MENINGKATKAN KEMAMPUAN MAKAN DENGAN SENDOK MELALUI PENDEKATAN KONTEKSTUAL BAGI ANAK TUNAGRAHITA SEDANG - Asminarti - Asminarti (Jurnal Penelitian Pendidikan Khusus, 2013)
Upgrading Eat With Spoons Contextual Approach For Children Tunagrahita Medium (Classroom Action Research Class 1 SLBN Tanjungpinang). The research was motivated by the problems that appear in the field in four children were grade DI tunagrahita SLB Tanjungpinang State, who have difficulty in eating with a spoon. This is evident from the ability to start a child in the child eat with spoon AT and DK difficulty in eating with a spoon.This study aims to improve children's ability to eat with a spoon through a contextual approach and methods of demonstration. Demonstration method is one method in which teachers demonstrate a process of activities in front of the students, after notice demonstrators students perform the same activities as demonstrated. The demonstration is intended that the child can understand the concept of teaching in performing a skill / skills through direct experience. The research methodology used was action research (Classroom Action Research), which takes the form of a collaborator with colleagues. Subjects were four children, mental retardation were one base class (D.1-C1) in SLB Tanjungpinang Affairs.Results of research conducted in the cycle I've seen an increase in children MR and SB was able to eat with a spoon, but need guidance in eating with a spoon. In general, they've seen the ability to eat with a spoon through a contextual approach. In the second cycle more visible in children's ability to skillfully eat with a spoon. It can be concluded that the contextual approach can improve the child's ability in mental retardation were eating with a spoon.